PERANCANGAN SISTEM PAKAR TIPE KEPRIBADIAN MENGGUNAKAN METODE FORWARD CHAINING BERBASIS WEB - Darmansah Darmansah Darmansah; Ilham Chairuddin; Tomy Nanda Putra (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2021)
Psychology is a science in the field of health that studies the behavior or personality of an individual (human). There are many ways that individuals can use to see their personality, one of which comes to a psychologist. This of course makes time inefficient because visiting a psychologist to find out his personality is also not cheap. Seeing this, the researcher made an expert system design that can be used by all individuals to be able to find out their personality type, both strengths, weaknesses, and what the suitable job of a personality type is. Expert system is a system that translates and takes decisions of an expert in their field into a system that can be implemented by humans. The method that researchers use in this case is forward chaining and web-based. The forward chaining method is a method that traces the data entered at the beginning and then will produce or issue a result or conclusion. With the construction of this system, an individual can easily find out the type of personality he has as well as the strengths, weaknesses and jobs that match the type he has without having to visit a psychologist. In general, there are four (four) personality types that an individual has, namely choleric, plagiarism, sanguine and melancholy.